Facile Strategy to Low-Cost Synthesis of Hierarchically Porous, Active Carbon of High Graphitization for Energy Storage - Deng, X.; Shi, W.; Zhong, Y.; Zhou, W.; Liu, M.; Shao, Zongping (American Chemical Society, 2018)
© 2018 American Chemical Society. To achieve high energy/power output, long serving life, and low cost of carbon-based electrodes for energy storage, we have developed a unique synthesis method for the fabrication of hierarchically porous carbon of high graphitization (HPCHG), derived from pyrolysis of an iron-containing organometallic precursor in a molten ZnCl2 media at relatively low temperatures. The as-prepared HPCHG has a large specific surface area (>1200 m2 g-1), abundant micro/mesopores, and plenty of surface defects. When tested in a supercapacitor (SC), the HPCHG electrode delivers 248 F g-1 at 0.5 A g-1 and a high capacitance retention of 52.4% (130 F g-1) at 50 A g-1. When tested in a sodium-ion battery (SIB), the HPCHG electrode exhibits a reversible capacity of 322 mA h g-1 at 100 mA g-1 while maintaining ~75% of the initial stable capacity after 2000 cycles with the applied current density as high as 5000 mA g-1, implying that the HPCHG electrode is very promising for energy storage.